2022
DOI: 10.1001/jamanetworkopen.2022.30858
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Family Representation in Randomized Clinical Trials Published in 3 Medical and Surgical Journals

Abstract: IMPORTANCEPatient and family engagement in research may improve the design, conduct, and dissemination of clinical research, but little is known about whether these stakeholder groups are involved in the design and conduct of randomized clinical trials. OBJECTIVE To characterize the involvement and role of patient and family representatives in the design and conduct of randomized clinical trials by reviewing randomized clinical trials from 3 peerreviewed medical and surgical journals with high impact factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…A systematic review of randomized clinical trials found that only 5% of studies included patient, family, or community participation. Further, the stakeholders' involvement was mainly in the implementation phase, underscoring the importance of augmenting stakeholder engagement across the entire spectrum of research [57]. The Black Impact study, our community-based clinical trial, stands out as an exemplary model in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of randomized clinical trials found that only 5% of studies included patient, family, or community participation. Further, the stakeholders' involvement was mainly in the implementation phase, underscoring the importance of augmenting stakeholder engagement across the entire spectrum of research [57]. The Black Impact study, our community-based clinical trial, stands out as an exemplary model in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Previous reviews of RCTs found low prevalence of PPI, with inconsistent reporting. [15][16][17][18][19][20][21] However, no trial-specific reporting guidelines require authors to indicate whether their trial included PPI (although the generic Guidance for Reporting Involvement of Patients and the Public [GRIPP2] 22 checklist may be used when PPI was part of an intervention), and journals rarely require PPI to be reported. 17 Relying…”
mentioning
confidence: 99%